2014
DOI: 10.1097/bcr.0000000000000062
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Bacterial Infection and Empirical Antibiotic Use in Toxic Epidermal Necrolysis Patients

Abstract: The objective of this study was to determine rates of positive bacterial cultures in patients with extensive toxic epidermal necrolysis, the rate of bacteremia, whether empirical antibiotics had been commenced, and their effectiveness when commenced. The authors conducted a retrospective chart review of patients with extensive toxic epidermal necrolysis between January 2001 and December 2012 admitted to the Victorian Adult Burns Service, Melbourne, Australia, with respect to the amount of positive cultures, nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…113 Antibiotic-therapy should be tailored to culture data 12,113,114 and local antibiogram. 115 Data suggest Staphylococcus aureus, Pseudomonas aeruginosa, and Enterobacteriaceae organisms are the most common causes of blood stream infection in SJS/TEN. 106 Patients with SJS/TEN may develop neutropenia, especially in severe cases.…”
Section: Infection Surveillancementioning
confidence: 99%
“…113 Antibiotic-therapy should be tailored to culture data 12,113,114 and local antibiogram. 115 Data suggest Staphylococcus aureus, Pseudomonas aeruginosa, and Enterobacteriaceae organisms are the most common causes of blood stream infection in SJS/TEN. 106 Patients with SJS/TEN may develop neutropenia, especially in severe cases.…”
Section: Infection Surveillancementioning
confidence: 99%
“…Antiviral treatments deployed initially do not treat secondary bacterial infections (15). The preferred treatment for bacterial infections is generally broad-spectrum antibiotics, but this can result in undesirable side effects that have a negative impact on the normal microflora of the host (16)(17)(18). Susceptible individuals within a population can be protected from risk of some common bacterial pathogens that are also capable to cause secondary infections, for example pneumonia, if vaccines are available; furthermore, the immune system is often capable of fighting bacterial infections alone, while during a virus-bacterial infection, the complex immune responses might be inapt to eliminate bacterial-induced disease complications (19).…”
Section: Introductionmentioning
confidence: 99%
“…Secondary bacterial infection is a common cause of morbidity in TEN patients and the high rate of infection in TEN patients has been confirmed by previous studies (Table ). Rajaratnam et al found a rate of infection of 85.7% and the lowest rate reported in the last 10 years is 62.9% . Septicemia has been described as the most frequent cause of death in TEN patients and it is validated as a factor increasing mortality .…”
Section: Discussionmentioning
confidence: 99%